Adaptive technologies and co-design strategies for historic spaces rehabilitation - Jacopo Gaspari; Andrea Boeri; Valentina Gianfrate; Danila Longo (Techne, 2017)
The renewed interest for under used sites of historical city centres is addressing a change in design paradigms on existing buildings involving local communities in the process from the very beginning. The paper reports a recent cooperation, named “Anteprima Lab”, between the Department of Architecture (DA) of University of Bologna, the City of Bologna and Urban Center. The action is intended as an enabler of initiatives aimed at enhancing those places assumed as common goods by local communities. The pilot defined the functional and spatial features of an innovative participated environment that follows the socio-political trends characterizing the modern age of Bologna.